Swords into Market Shares: Technology, Economics, and Security in the New Russia - Schweitzer, Glenn E. (The National Academies Press, 2000)
While researching this book, Glenn Schweitzer met four Moscow physicists who were trying to license Russian technology to western firms for product manufacture. During the worst times, they were reduced to driving taxis to keep things afloat. He asked them, will technological innovation have a discernible impact on the Russian economy in the coming decade? No, was the immediate reply. Are they right? In Swords into Market Shares, Schweitzer examines the roots of such pessimism and the prospects for Russia to prosper from its technology in the post-Soviet world. He explores the different visions of prosperity held by entrepreneurs, technologists, and government officials and goes on to examine the barriers to progress as Russia struggles to build a viable technology industry on its own terms. In accessible language, this book talks about technology's place within Russia's economy and its research and development infrastructure. Schweitzer looks at the impact of the Soviet legacy—central planning, lack of priorities, scant incentives for personal initiative—and the aftermath of the Russian financial meltdown of 1998. He also reviews the experiences of American companies that have invested in Russian technology and examines the results of pressure to reform according to the economic model of the West. Schweitzer goes on to document the problems of economic crime and government corruption, which plague activities designed to generate income in Russia. He discusses the lack of protection for intellectual property and taxation issues that stand in the way of technological innovation. The book looks at the impact of the "brain drain" as Russian experts seek greener pastures—not only the ominous recruitment of Russian biological weapons experts and the acquisition of military technology by "rogue" nations—but also Russia's own program to sell military technology for badly needed funds. Schweitzer's use of case studies and examples puts a human face on these issues. He also discusses Russia's 60 "science cities"—sites of state research centers—with close-ups of three "nuclear cities." Can the technical strengths of the Soviet military complex find a place in civilian Russia? How can this vast country sustain even a minimal standard of living? Swords into Market Shares addresses these and other key questions and explores fundamental policy issues confronting both Russia and the United States as Russia struggles for an economic foothold.
Keywords: Policy for Science and Technology

Long-Term Institutional Management of U.S. Department of Energy Legacy Waste Sites - National Research Council (The National Academies Press, 2000)
It is now becoming clear that relatively few U.S. Department of Energy (DOE) waste sites will be cleaned up to the point where they can be released for unrestricted use. "Long-term stewardship" (activities to protect human health and the environment from hazards that may remain at its sites after cessation of remediation) will be required for over 100 of the 144 waste sites under DOE control (U.S. Department of Energy, 1999). After stabilizing wastes that remain on site and containing them as well as is feasible, DOE intends to rely on stewardship for as long as hazards persist—in many cases, indefinitely. Physical containment barriers, the management systems upon which their long-term reliability depends, and institutional controls intended to prevent exposure of people and the environment to the remaining site hazards, will have to be maintained at some DOE sites for an indefinite period of time. The Committee on Remediation of Buried and Tank Wastes finds that much regarding DOE's intended reliance on long-term stewardship is at this point problematic. The details of long-term stewardship planning are yet to be specified, the adequacy of funding is not assured, and there is no convincing evidence that institutional controls and other stewardship measures are reliable over the long term. Scientific understanding of the factors that govern the long-term behavior of residual contaminants in the environment is not adequate. Yet, the likelihood that institutional management measures will fail at some point is relatively high, underscoring the need to assure that decisions made in the near term are based on the best available science. Improving institutional capabilities can be expected to be every bit as difficult as improving scientific and technical ones, but without improved understanding of why and how institutions succeed and fail, the follow-through necessary to assure that long-term stewardship remains effective cannot reliably be counted on to occur. Long-Term Institutional Management of U.S. Department of Energy Legacy Waste Sites examines the capabilities and limitations of the scientific, technical, and human and institutional systems that compose the measures that DOE expects to put into place at potentially hazardous, residually contaminated sites.
Keywords: Environment and Environmental Studies

Long-Term Research Needs for High-Level Waste at Department of Energy Sites: Interim Report (The National Academies Press, 2000)
Keywords: Environment and Environmental Studies

Interim Report for the Committee on Long-Term Research Needs for Deactivation and Decommissioning at Department of Energy Sites (The National Academies Press, 2000)
Keywords: Environment and Environmental Studies

Engineering Challenges to the Long-Term Operation of the International Space Station - National Research Council (The National Academies Press, 2000)
The International Space Station (ISS) is truly an international undertaking. The project is being led by the United States, with the participation of Japan, the European Space Agency, Canada, Italy, Russia, and Brazil. Russia is participating in full partnership with the United States in the fabrication of ISS modules, the assembly of ISS elements on orbit, and, after assembly has been completed, the day-to-day operation of the station. Construction of the ISS began with the launch of the Russian Zarya module in November 1998 followed by the launch of the U.S. Unity module in December 1998. The two modules were mated and interconnected by the crew of the Space Shuttle during the December flight, and the first assembled element of the ISS was in place. Construction will continue with the delivery of components and assembly on orbit through a series of 46 planned flights. During the study period, the Assembly Complete milestone was scheduled for November 2004 with the final ISS construction flight delivering the U.S. Habitation Module. Engineering Challenges to the Long-Term Operation of the International Space Station is a study of the engineering challenges posed by longterm operation of the ISS. This report states that the National Aeronautics and Space Administration (NASA) and the ISS developers have focused almost totally on completing the design and development of the station and completing its assembly in orbit. This report addresses the issues and opportunities related to long-term operations.
Keywords: Space and Aeronautics

Improving Operations and Long-Term Safety of the Waste Isolation Pilot Plant: Interim Report - National Research Council (The National Academies Press, 2000)
The National Research Council convened a committee of experts to advise the U.S. Department of Energy (DOE) on the operation of the Waste Isolation Pilot Plant (WIPP), a geologic repository for disposal of defense transuranic (TRU) waste near Carlsbad, New Mexico. The committee was asked to provide recommendations on the following two issues: (1) a research agenda to enhance confidence in the long-term performance of WIPP; and (2) increasing the throughput, efficiency, and cost-benefit without compromising safety of the National TRU Program for characterizing, certifying, packaging, and shipping waste to WIPP. The committee has written this interim report to provide DOE with recommendations on several issues that the committee believes merit immediate consideration and action. In developing this report, the committee has been guided by the principle of "reasonableness" with respect to risks, costs, and the ALARA (as low as reasonably achievable) principle. In the committee's judgment, implementing the recommendations contained in this report will contribute to the continued safe operation of WIPP.
Keywords: Environment and Environmental Studies

Alternatives for High-Level Waste Salt Processing at the Savannah River Site - National Research Council (The National Academies Press, 2000)
The Second World War introduced the world to nuclear weapons and their consequences. Behind the scene of these nuclear weapons and an aspect of their consequences is radioactive waste. Radioactive waste has varying degrees of harmfulness and poses a problem when it comes to storage and disposal. Radioactive waste is usually kept below ground in varying containers, which depend on how radioactive the waste it. High-level radioactive waste (HLW) can be stored in underground carbon-steel tanks. However, radioactive waste must also be further immobilized to ensure our safety. There are several sites in the United States where high-level radioactive waste (HLW) are stored; including the Savannah River Site (SRS), established in 1950 to produce plutonium and tritium isotopes for defense purposes. In order to further immobilize the radioactive waste at this site an in-tank precipitation (ITP) process is utilized. Through this method, the sludge portion of the tank wastes is being removed and immobilized in borosilicate glass for eventual disposal in a geological repository. As a result, a highly alkaline salt, present in both liquid and solid forms, is produced. The salt contains cesium, strontium, actinides such as plutonium and neptunium, and other radionuclides. But is this the best method? The National Research Council (NRC) has empanelled a committee, at the request of the U.S. Department of Energy (DOE), to provide an independent technical review of alternatives to the discontinued in-tank precipitation (ITP) process for treating the HLW stored in tanks at the SRS. Alternatives for High-Level Waste Salt Processing at the Savannah RIver Site summarizes the finding of the committee which sought to answer 4 questions including: "Was an appropriately comprehensive set of cesium partitioning alternatives identified and are there other alternatives that should be explored?" and "Are there significant barriers to the implementation of any of the preferred alternatives, taking into account their state of development and their ability to be integrated into the existing SRS HLW system?"
Keywords: Environment and Environmental Studies

Buzzwords: A Scientist Muses on Sex, Bugs, and Rock 'n' Roll - Berenbaum, May R. (The National Academies Press, 2000)
What sort of person devotes their life to the study of bugs? How do you picture your average, every-day entomologist? "I've been photographed on several occasions," writes author May Berenbaum, "and it seems that every time, photographers ask me to pose in one of three ways: seated in front of a microscope, with an insect (usually a cockroach) on my face, or with an insect net clutched in my hand." In Buzzwords, Berenbaum expertly blows away these stereotypes with short takes on all things entomological—from the story of a pet ant kept for 14 years to major motion pictures featuring cockroaches. Buzzwords showcases the Best of Berenbaum, a selection from her humor column in the American Entomologist professional journal, accompanied by a number of original pieces written for this book. "I know people are reading these columns," she notes, "because they write me letters that point out all the mistakes I've made!" The book comes in four parts:
Keywords: Explore Science; Agriculture

Einstein's Unfinished Symphony: Listening to the Sounds of Space-Time - Bartusiak, Marcia (The National Academies Press, 2000)
A new generation of observatories, now being completed worldwide, will give astronomers not just a new window on the cosmos but a whole new sense with which to explore and experience the heavens above us. Instead of collecting light waves or radio waves, these novel instruments will allow astronomers to at last place their hands upon the fabric of space-time and feel the very rhythms of the universe. These vibrations in space-time—or gravity waves—are the last prediction of Einstein's general theory of relativity yet to be observed directly. They are his unfinished symphony, waiting nearly a century to be heard. When they finally reveal themselves to astronomers, we will for the first time be able to hear the cymbal crashes from exploding stars, tune in to the periodic drumbeats from swiftly rotating pulsars, listen to the extended chirps from the merger of two black holes, and eavesdrop on the remnant echoes from the mighty jolt of the Big Bang itself. When Einstein introduced general relativity in 1915, it was hailed as a momentous conceptual achievement. Einstein attained celebrity status. But, once scientists verified what they could of the theory, given the scant experiments available at the time, general relativity became "largely a theoretical curiosity," writes Marcia Bartusiak. Now, after decades of technological advancement, general relativity is being tested with unprecedented accuracy. It even affects our everyday lives. Satellites used by both travelers and soldiers to peg their positions require constant corrections of Einsteinian precision. Meanwhile, the first gravity-wave "telescopes"—including the LIGO facility—are about to come alive. In Einstein's Unfinished Symphony, Bartusiak captures the excitement as two gravity-wave observatories in Louisiana and Washington State, as well as others in Italy, Germany, and Japan, approach operation and physicists gear up to begin their work to register the long-predicted quakes in space-time. With each chapter, Bartusiak continues her musical metaphor in tracing the story of general relativity, from the time "Maestro" Einstein enters physics, through the "Starlight Waltz" of neutron stars twisting space-time around themselves, to the "Dissonant Chords" of controversy as physicists fight to get their radically new observatories approved, through the "Finale" as a worldwide endeavor in gravity-wave astronomy is launched.
Keywords: Explore Science; Math, Chemistry, and Physics

Summary of the June 2000 Meeting of the Clinical Research Roundtable - Institute of Medicine (The National Academies Press, 2000)
On June 27-28 of 2000, the 28-member Clinical Research Roundtable (CRR) met meeting to learn about each other's backgrounds and experiences as well as explore their interests and priorities for future work by the CRR. The June meeting was primarily organizational in nature, as the 28 members learned about each other's backgrounds and experiences and explored their interests and priorities for future work by the CRR. The group concluded by breaking into four subgroups to explore potential activities in areas such as data collection and career development. Summary of the Jun 2000 Meeting of the Clinical Research Roundtable summarizes this meeting and includes information on the invited talks of the gathering.

Space Studies Board Annual Report 1999 (The National Academies Press, 2000)

Designing a Market Basket for NAEP: Summary of a Workshop - National Research Council (The National Academies Press, 2000)
At the request of the U.S. Department of Education, the National Research Council (NRC) established the Committee on NAEP Reporting Practices to examine the feasibility and potential impact of district-level and market-basket reporting practices. As part of its charge, the committee sponsored a workshop in February 2000 to gather information on issues related to market-basket reporting for the National Assessment of Education Progress (NAEP). Designing a Market Basket for NAEP: Summary of a Workshop explores with various stakeholders their interest in and perceptions regarding the desirability, feasibility, and potential impact of market-basket reporting for the NAEP. The market-basket concept is based on the idea that a relatively limited set of items can represent some larger construct. The general idea of a NAEP market basket is based on an image of a collection of test questions representative of some larger content domain and an easily understood index to summarize performance on the items.
Keywords: Education

Strategies to Protect the Health of Deployed U.S. Forces: Detecting, Characterizing, and Documenting Exposures - National Research Council (The National Academies Press, 2000)
Since Operation Desert Shield/Desert Storm, Gulf War veterans have expressed concerns about health effects that could be associated with their deployment and service during the war. Although similar concerns were raised after other military operations, the Gulf War deployment focused national attention on the potential, but uncertain, relationship between the presence of chemical and biological (CB) agents and other harmful agents in theater and health symptoms reported by military personnel. Strategies to Protect the Health of Deployed U.S. Forces which is one of the four two-year studies, examines the detection and tracking of exposures of deployed personnel to multiple harmful agents.
Keywords: Health and Medicine; Environment and Environmental Studies; Conflict and Security Issues

Integrated Design of Alternative Technologies for Bulk-Only Chemical Agent Disposal Facilities - National Research Council (The National Academies Press, 2000)
The U.S. Army is pilot testing chemical hydrolysis as a method for destroying the chemical agents stockpiled at Aberdeen, Maryland (HD mustard agent), and Newport, Indiana (VX nerve agent). The chemical agents at both locations, which are stored only in bulk ton containers, will be hydrolyzed (using aqueous sodium hydroxide for VX and water for HD) at slightly below the boiling temperature of the solution. The resulting hydrolysate at Aberdeen, which will contain thiodiglycol as the primary reaction product, will be treated by activated sludge biodegradation in sequencing batch reactors to oxidize organic constituents prior to discharge to an on-site federally owned wastewater treatment facility. The hydrolysate at Newport, which will contain a thiol amine and methyl phosphonic acid as the major reaction products, is not readily amenable to treatment by biodegradation. Therefore, organic constituents will be treated using supercritical water oxidation (SCWO). Integrated Design of Alternative Technologies for Bulk-Only Chemical Agent Disposal Facilities focuses on the overarching issues in the process designs integrating individual processing steps, including potential alternative configurations and process safety and reliability. This report reviews the acquisition design packages (ADPs) for the ABCDF and NECDF prepared by Stone and Webster Engineering Company for the U.S. Army.
Keywords: Engineering and Technology; Environment and Environmental Studies

Developing Technologies for Early Detection of Breast Cancer: A Public Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2000)
In November 1999, the Institute of Medicine, in consultation with the Commission on Life Sciences, the Commission on Physical Sciences, Mathematics, and Applications, and the Board on Science, Technology and Economic Policy launched a one year study on technologies for early detection of breast cancer. The committee was asked to examine technologies under development for early breast cancer detection, and to scrutinize the process of medical technology development, adoption, and dissemination. The committee is gathering information on these topics for its report in a number of ways, including two public workshops that bring in outside expertise. The first workshop on "Developing Technologies for Early Breast Cancer Detection" was held in Washington DC in February 2000. The content of the presentations at the workshop is summarized here. A second workshop, which will focus on the process of technology development and adoption, will be held in Washington, DC on June 19-20. A formal report on these topics, including conclusions and recommendations, will be prepared by the committee upon completion of the one-year study.
Keywords: Health and Medicine

One Universe: At Home in the Cosmos - Tyson, Neil de Grasse; Liu, Charles; Irion, Robert (The National Academies Press, 2000)
A new window opens onto the cosmos... Almost every day we are challenged by new information from the outermost reaches of space. Using straightforward language, One Universe explores the physical principles that govern the workings of our own world so that we can appreciate how they operate in the cosmos around us. Bands of color in a sunlit crystal and the spectrum of starlight in giant telescopes, the arc of a hard-hit baseball and the orbit of the moon, traffic patterns on a freeway and the spiral arms in a galaxy full of stars—they're all tied together in grand and simple ways. We can understand the vast cosmos in which we live by exploring three basic concepts: motion, matter, and energy. With these as a starting point, One Universe shows how the physical principles that operate in our kitchens and backyards are actually down-to-Earth versions of cosmic processes. The book then takes us to the limits of our knowledge, asking the ultimate questions about the origins and existence of life as we know it and where the universe came from—and where it is going. Glorious photographs—many seen for the first time in these pages—and original illustrations expand and enrich our understanding. Evocative and clearly written, One Universe explains complex ideas in ways that every reader can grasp and enjoy. This book captures the grandeur of the heavens while making us feel at home in the cosmos. Above all, it helps us realize that galaxies, stars, planets, and we ourselves all belong to One Universe.
Keywords: Explore Science; Space and Aeronautics

Natural Attenuation for Groundwater Remediation (The National Academies Press, 2000)
In the past decade, officials responsible for clean-up of contaminated groundwater have increasingly turned to natural attenuation-essentially allowing naturally occurring processes to reduce the toxic potential of contaminants-versus engineered solutions. This saves both money and headaches. To the people in surrounding communities, though, it can appear that clean-up officials are simply walking away from contaminated sites. When is natural attenuation the appropriate approach to a clean-up? This book presents the consensus of a diverse committee, informed by the views of researchers, regulators, and community activists. The committee reviews the likely effectiveness of natural attenuation with different classes of contaminants-and describes how to evaluate the "footprints" of natural attenuation at a site to determine whether natural processes will provide adequate clean-up. Included are recommendations for regulatory change. The committee emphasizes the importance of the public's belief and attitudes toward remediation and provides guidance on involving community stakeholders throughout the clean-up process. The book explores how contamination occurs, explaining concepts and terms, and includes case studies from the Hanford nuclear site, military bases, as well as other sites. It provides historical background and important data on clean-up processes and goes on to offer critical reviews of 14 published protocols for evaluating natural attenuation.
Keywords: Environment and Environmental Studies

The Aging Mind: Opportunities in Cognitive Research - National Research Council (The National Academies Press, 2000)
Possible new breakthroughs in understanding the aging mind that can be used to benefit older people are now emerging from research. This volume identifies the key scientific advances and the opportunities they bring. For example, science has learned that among older adults who do not suffer from Alzheimer's disease or other dementias, cognitive decline may depend less on loss of brain cells than on changes in the health of neurons and neural networks. Research on the processes that maintain neural health shows promise of revealing new ways to promote cognitive functioning in older people. Research is also showing how cognitive functioning depends on the conjunction of biology and culture. The ways older people adapt to changes in their nervous systems, and perhaps the changes themselves, are shaped by past life experiences, present living situations, changing motives, cultural expectations, and emerging technology, as well as by their physical health status and sensory-motor capabilities. Improved understanding of how physical and contextual factors interact can help explain why some cognitive functions are impaired in aging while others are spared and why cognitive capability is impaired in some older adults and spared in others. On the basis of these exciting findings, the report makes specific recommends that the U.S. government support three major new initiatives as the next steps for research.
Keywords: Behavioral and Social Sciences; Health and Medicine

Evaluation of Demonstration Test Results of Alternative Technologies for Demilitarization of Assembled Chemical Weapons: A Supplemental Review - National Research Council (The National Academies Press, 2000)
In 1996, the U.S. Congress enacted two laws, Public Law 104-201 (authorization legislation) and Public Law 104-208 (appropriation legislation), mandating that the U.S. Department of Defense (DOD) conduct an assessment of alternative technologies to the baseline incineration process for the demilitarization of assembled chemical munitions. The PMACWA had previously requested that the National Research Council (NRC) perform and publish an independent evaluation of the seven technologies packages that had been selected during earlier phases of the Assembled Chemical Weapons Assessment (ACWA) program and deliver a report by September 1, 1999. However, to meet that deadline, the NRC Committee on Review and Evaluation of Alternative Technologies for Demilitarization of Assembled Chemical Weapons (ACW Committee) had to terminate its data-gathering activities on March 15, 1999, prior to the completion of demonstration tests. In September 1999, the PMACWA requested that the ACW Committee examine the reports of the demonstration tests and determine if the results changed the committee's original findings, recommendations, and comments. Evaluation of Demonstration Test Results of Alternative Technologies for Demilitarization of Assembled Chemical Weapons documents the committee's reassessment of the findings and recommendations in the original report, Review and Evaluation of Alternative Technologies for Demilitarization of Assembled Chemical Weapons.
Keywords: Environment and Environmental Studies; Math, Chemistry, and Physics

International Conflict Resolution After the Cold War - National Research Council (The National Academies Press, 2000)
The end of the Cold War has changed the shape of organized violence in the world and the ways in which governments and others try to set its limits. Even the concept of international conflict is broadening to include ethnic conflicts and other kinds of violence within national borders that may affect international peace and security. What is not yet clear is whether or how these changes alter the way actors on the world scene should deal with conflict:
Keywords: Conflict and Security Issues; Behavioral and Social Sciences